2019
DOI: 10.1080/24750263.2018.1558294
|View full text |Cite
|
Sign up to set email alerts
|

Bovine satellite DNAs – a history of the evolution of complexity and its impact in the Bovidae family

Abstract: Despite the many questions regarding satellite DNA sequences and their cellular roles, the evolutionary history of eukaryotic genomes seems to have been largely influenced by this dynamic and multifaceted genomic component. The bovine genome is highly rich in diverse satDNA sequences that differ in monomer sequence and length, complexity, chromosomal location and abundance, as well as in their sequences' evolutionary mechanisms. In the evolution of the Bovidae family, the genomes' repetitive fraction played a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 133 publications
0
14
0
Order By: Relevance
“…1993, 1996; Chaves et al. 2000, 2005), unlike families named SAT1.723 , SATIV , SAT1.711a , and SAT1.711b that are not in all Pecora, although results are somewhat equivocal (Escudeiro et al. 2019).…”
Section: Introductionmentioning
confidence: 91%
“…1993, 1996; Chaves et al. 2000, 2005), unlike families named SAT1.723 , SATIV , SAT1.711a , and SAT1.711b that are not in all Pecora, although results are somewhat equivocal (Escudeiro et al. 2019).…”
Section: Introductionmentioning
confidence: 91%
“…The dynamic nature of repetitive elements is clearly a basilar reason for genomic plasticity (e.g., [14,102,142,143]) and it is in fact a way of having a low impact on the euchromatic genome [14,97]. Today, an increasing body of evidence strongly validates the involvement of satDNA in the modulation of genomic architectures of a large number of taxa, as in the case of bovids [21,104,144,145], rodents [17,111,143,146], suiformes [57] or genets [147]. This largely extends beyond mammalian evolution, as it can also be observed in insects (e.g., [54,148]), reptiles (e.g., [149]), plants [150] and many other lineages.…”
Section: Modulating Genome Architecture With Satdnasmentioning
confidence: 99%
“…The analyses of the sequences at the breakpoint regions preceding a translocation are of great importance in understanding the translocation event [21,131]. These sequences are essentially centromeric satDNAs, whose detailed physical and organizational analysis contributed much to better comprehend the chromosomal mechanism behind the rob (1;29) translocation [20,145].…”
Section: Remodeling Genome Architecture Through Robertsonian Translocmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, several studies have demonstrated that satDNAs, especially those found in centromeres, are associated with Robertsonian translocations, the main chromosome rearrangements related to Bovidae genome evolution 5,[52][53][54][55] . It would be interesting to investigate if there is also a link between satDNAs and chromosome rearrangements in Xenarthra, as the number of available genomes of this group will certainly increase in the near future.…”
Section: Discussionmentioning
confidence: 99%